Alternative Media Based on Papaya and Fish Extract for Glutathione Production in Saccharomyces cerevisiae: Production of Glutathione by Papaya and Fish Extracts (Biological Sciences - PJSIR, 2019)
Glutathione (GSH) is an antioxidant that functions to protect cells from oxidative stress. It is used for medical purposes, as an additive in foods and cosmetics industry. The magnitude of these applications results in increased demand for glutathione every year, however, the cost of glutathione is high. The production of glutathione using an alternative source for the medium and the amino acids used in the media might be the solution for managing the high cost of glutathione production in yeast. This study uses an alternative media based on papaya and fish extract to reduce production costs. The fish extract contains glutamate, cysteine and glycine that can be utilised as a source of amino acid. This study suggested that media based on papaya extract could be employed to produce glutathione in yeast Saccharomyces cerevisiae. Moreover, administration of 5 mg/mL of fish extract could increase the glutathione production up to 36.36% as compared to a control. The optimum production of glutathione was obtained in a harvest time of 44 h culture. Therefore, further investigation by modifying the medium is warranted to produce glutathione in a cost friendly manner in the S. cerevisiae.